Technological and protective performance of LAB isolated from Serpa PDO cheese: Towards selection and development of an autochthonous starter culture - Araújo-Rodrigues, Helena (2022)
Serpa is an ovine raw milk cheese widely appreciated by the consumers. However, raw milk products may be seen with reservations in terms of safety or technological defects. To overcome that, the addition of an autochthonous starter culture may ensure the cheesemaking process optimization and microbiota dominance. In this work, the technological and protective performance of eleven lactic acid bacteria strains, isolated from Serpa Protected Designation of Origin cheese and reported as generally recognized as safe, were screened. The inte-gration of technological and protective properties studied in the PCA plot, coupled with the proteolytic and lipolytic analysis suggested that Lb. plantarum PL1 and PL4 strains may be the best candidates. These strains showed both proteolytic and lipolytic activities, a good acidification potential, low D-lactic acid production and were well adapted to the salt and temperatures used. PL1 strain also exhibited a higher antimicrobial effect against the pathogenic bacteria studied. Although Lb. paracasei strain showed lower acidification capacity, due to their technological and protective properties, it could be combined with other more acidifying strains. As future work, it is important to establish cheese model systems to complement this screening and implement an autochthonous starter culture.